Hydrogen separation from synthesis gas using silica membrane: CFD simulation. (31st July 2020) - Tahmasbi, Davood; Hossainpour, Siamak; Babaluo, Ali Akbar; Rezakazemi, Mashallah; Mousavi Nejad Souq, Seyyed Sajad; Younas, Mohammad
Abstract: In the present article, an axisymmetric two-dimensional (2D) computational fluid dynamic (CFD) model was adapted to predict the efficiency of the silica membrane for hydrogen (H2 ) separation as a renewable energy source. In this model, continuum flows on the shell and tube sides are defined through the Navier-Stokes and transport of chemical species equations. Components transfer through the silica membrane is characterized by introducing source-sink terms based on activating transport mechanisms. To validate the presented model results related to H2 molar fraction at the retentate and permeate sides were compared with experimental data. The CFD model prognosticates the local information of velocity distribution and the molar fraction of the components. Finally, considering the effects of temperature, pressure difference, gas flow rate, and inner radius of the module on the H2 molar fraction, silica membrane performance was investigated. Moreover, it has been shown that with increasing working temperature from 323 to 473 K, H2 molar fraction at the shell side decreases from 59% to 28.4%, and in the tube side, it rises from 78.8% to 82.8%. On the shell side, it could be seen that H2 permeates better for a low gas flow rate. At the tube side, this parameter has a positive effect on H2 purification. The result of the impact of pressure differences at shell and tube sides was used to indicate the variation in the H2 molar fraction. An increase in pressure difference causes a decrease of H2 molar fraction at the tube side. At the shell side, H2 molar fraction would be decreased with an addition in pressure difference from 1 to 3 bar. Any further pressure difference rise from 3 to 4 bar, make this trend ascending. Likewise, at the shell and tube sides, by enhancing the inner radius of the module, the molar fraction of H2 increases. Highlights: 2D axisymmetric CFD model is presented for H2 separation as a renewable energy. Model includes simultaneous transport of components through silica membrane. The proposed model is verified using experimental data. Evaluation of membrane performance is presented at different conditions.